Exploring Thai EFL Learners' Preferences for Speaking Activities - Beding, Brigette (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2024)
This study aimed to determine the preferred speaking activities of Thai EFL learners and to explore the rationale behind their preferences. The participants were 44 first-year English major students enrolled in the Listening and Speaking in Daily Life course at the University of Phayao, Thailand. The participants were selected through convenience sampling. Data were collected using a questionnaire and semi-structured interviews and analyzed through descriptive statistics and content analysis. The results showed that Thai EFL learners most preferred engaging in language games (79.55%), conversations (70.45%), role plays (65.91%), pronunciation drills (61.36%), and describing pictures (59.09%). Other speaking activities were less preferred. Findings from the interviews with 11 participants further supported these preferences, revealing that learners found the top five activities to be motivating, relaxing, and enjoyable. Participants noted that these activities encouraged group work, provided more opportunities to speak the language, and helped them improve their speaking skills. Understanding learners' preferred speaking activities can help educators design teaching strategies and materials that resonate with students' needs, fostering a more supportive and effective language-learning environment.